Therapeutic success in fragmented coronoid process disease and other canine medial elbow compartment pathology: a systematic review with meta-analyses - Kähn, Hubertus; Zablotski, Yury; Meyer-Lindenberg, Andrea (Frontiers in Veterinary Science, 2023)
Introduction: The correct treatment of elbow dysplasia is controversial in modern small animal orthopedics. The aim of this study was to compile all relevant literature of the therapy of fragmented coronoid process and other hereditary disorders of the medial elbow compartment and to statistically evaluate the therapeutic results in three meta-analyses. Methods: The basis for the systematic literature review was a comprehensive database search of Web of Science, PubMed and Medline. Studies on living patients with above mentioned degenerative joint disease were included in the initial literature search. The data from the final studies, selected according to the PRISMA guidelines, was subsequently extracted. Finally, the success of the different therapies was compared and analyzed by three meta-analyses: success rate, mean difference and standardized mean difference. Results: 14 of 494 publications covered by the systematic literature search remained. Their overall truth was: In studies where surgery outcomes was determined by clinical examination and owner questionnaires, it was found that surgical intervention had a significant positive outcome in the presence of fragmented coronoid process and medial compartment disease. Surgical outcomes were also good in three cross-over studies that investigated treatment success using computerized gait analysis. In contrast, comparative studies between surgical and conservative management yielded controversial results. The meta-analysis found no significant difference between medical and surgical therapy. Discussion: The positive results of studies investigating owner satisfaction and veterinary clinical examination of surgical therapy for medial compartment disease were confirmed by two meta-analyses. However, their study designs were susceptible to observer biases. A third meta-analysis of standardized mean difference differentiating computerized gait analysis results of surgical and conservative management found no evidence of significant superiority of each treatment modality. It however had a limited number of subjects. More comparative studies of high evidence are needed to better understand medial compartment disease and provide the clinician with more accurate diagnostics to separate pathology that should be treated surgically from pathology that can benefit from conservative therapy similarly. Given the invasiveness a more cautious approach might be warranted regarding generally recommending surgery for pathology of the medial elbow compartment.